Rebuilding Communal Resilience: a Post Operational Social and Economic Impact Assessment of the Eastern Bulk Cement Company (Eagle Cement) in Rumuolumeni - Brown, Ibama (Uniplan: Journal of Urban and Regional Planning, 2025)
There is a phenomenal global departure from the industrialisation era to embrace the information age fuelled by artificial intelligence (AI). This intended transformation has engendered the abandonment of secondary production activities in urban societies. The study assessed the social and economic impact of the Eastern Bulk Cement Company (Eagle Cement) on the host community during operation, after decommissioning and eventual abandonment. The study employed a qualitative research approach and adopted a case study research design. The study found positive and negative social and economic impacts during their operative years and after decommissioning. The positive benefits include maintaining access roads, employment opportunities and improved living conditions. The negative impacts identified are insecurity, massive unemployment, poor road maintenance, inadequate healthcare facilities and services, and abandoned and derelict properties. The study findings recommend that the government of Rivers State should step in and reinvigorate the benefits scheme, especially the scholarship scheme for the host community to mitigate the adverse challenges faced by the host community; the community should ensure that the activity of the youth is brought under control to minimise the violent activities;   there should be a two-pronged collaborative effort between the government and the host community to ensure that all the abandoned sectors reinvigorated; and the government should make alternative arrangements with the community to ensure that the abandoned industrial site is being reacquired and put into proper use.